2012
DOI: 10.2478/s11756-012-0070-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and virulence of bacteria from Ostrinia nubilalis (Lepidoptera: Pyralidae)

Abstract: AbstractIsolation, characterization and virulence of the culturable bacteria from entire tissues of larval Ostrinia nubilalis (Hübner) (Lepidoptera: Pyralidae) were studied to obtain new microbes for biological control. A total of 16 bacteria were isolated from living and dead larvae collected from different maize fields in the Eastern Black Sea Region of Turkey. The bacterial microbiota of O. nubilalis were identified as Pseudomonas aeruginosa (On1), Brevundimonas aurantiaca (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…Among all the isolated strains, S. marcescensis was found to be most pathogenic one and showed ~73% mortality of the host (Gokce et al, 2010). Recently, it is reported that the gut of Ostrinia nubilalis harbors P. aeruginosa, Serratia sp., Variovorax paradoxus and S. marcescens bacterial strains which is found to be pathogenic against the host (Secil et al, 2012). These results confirm the presence of pathogenic stains in gut of different organisms and signify its vital role in disease development.…”
Section: Discussionsupporting
confidence: 76%
“…Among all the isolated strains, S. marcescensis was found to be most pathogenic one and showed ~73% mortality of the host (Gokce et al, 2010). Recently, it is reported that the gut of Ostrinia nubilalis harbors P. aeruginosa, Serratia sp., Variovorax paradoxus and S. marcescens bacterial strains which is found to be pathogenic against the host (Secil et al, 2012). These results confirm the presence of pathogenic stains in gut of different organisms and signify its vital role in disease development.…”
Section: Discussionsupporting
confidence: 76%
“…Out of which S. marcescens showed highest mortality (73%) against larvae within 10 days (Gokce et al, 2010). Similarly P. aeruginosa, Serratia sp., Variovorax paradoxus and S. marcescens associated with the gut of Ostrinia nubilalis (Hubner) have been reported to be pathogenic against their host (Secil et al, 2012). Çakici et al (2014) also documented the pathogenicity of internal bacteria of S. littoralis viz.…”
Section: Introductionmentioning
confidence: 96%
“…The most common species of this genus is A. faecalis which is commonly found in the intestinal canal of vertebrates, decaying materials, dairy products, water and soil (Busse and Stolz 2006). Alcaligenes faecalis has also been isolated from many insect species such as Ips sexdentatus (Boern) (Coleoptera: Curculionidae), Ostrinia nubilalis (Hübner) (Lepidoptera: Pyralidae) and Tapinoma melanocephalum (Fabricius) (Hymenoptera: Formicidae) (Sevim et al 2012a: Secil et al 2012: Pesquero et al 2012. We also isolated one strain of A. faecalis from P. operculella, showing a first isolation of this species from any stored product pest.…”
Section: Discussionmentioning
confidence: 99%